Development and application of a fully automatic multi-function cassette module Mortenon M1 for radiopharmaceutical synthesis - Cui, Fang-Bo; Lv, Xuan; Yan, Cheng-Long; Eng, Wai-Si; Yu, Shan-You; Zheng, Qi-Huang (Annals of nuclear medicine, 2024)
Introduction Functions of existing automatic module systems for synthesis of radiopharmaceuticals mainly focus on the radiolabeling of small molecules. There are few modules which have achieved full-automatic radiolabeling of non-metallic and metallic nuclides on small molecules, peptides, and antibody drugs. This study aimed to develop and test a full-automatic multifunctional module system for the safe, stable, and efficient production of radiopharmaceuticals. Methods According to characteristics of labeling process of radioactive drugs, using UG and Solidworks softwares, full-automatic cassette-based synthesis module system Mortenon M1 for synthesis of radiopharmaceuticals with various radionuclides, was designed and tested. Mortenon M1 has at least three significant highlights: the cassettes are disposable, and there is no need of manual cleaning; the synthesis method program is flexible and can be edited freely by users according to special needs; this module system is suitable for radiolabeling of both small-molecule and macromolecular drugs, with potentially various radionuclides including 18 F, 64 Cu, 68 Ga, 89 Zr, 177 Lu, etc. By program control methods for certain drugs, Mortenon M1 was used for radiolabeling of both small-molecule drugs such as [ 68 Ga]-FAPI-46 and macromolecular drugs such as [ 89 Zr]-TROP2 antibody. Quality control assays for product purity were performed with radio-iTLC and radio-HPLC, and the radiotracers were confirmed for application in microPET imaging in xenograft tumor-bearing mouse models. Results Functional tests for Mortenon M1 module system were conducted, with [ 68 Ga]-FAPI-46 and [ 89 Zr]-TROP2 antibody as goal synthetic products, and it displayed that with the cassette modules, the preset goals could be achieved successfully. The radiolabeling synthesis yield was good ([ 68 Ga]-FAPI-46, 70.63% ± 2.85%, n = 10; [ 89 Zr]-TROP2, 82.31% ± 3.92%, n = 10), and the radiochemical purity via radio-iTLC assay of the radiolabeled products was above 99% after purification. MicroPET imaging results showed that the radiolabeled tracers had reasonable radioactive distribution in MDA-MB-231 and SNU-620 xenograft tumor-bearing mice, and the tumor targeted radiouptake was satisfactory for diagnosis. Conclusion This study demonstrated that the full-automatic module system Mortenon M1 is efficient for radiolabeling synthesis of both small-molecule and macromolecular substrates. It may be helpful to reduce radiation exposure for safety, provide qualified radiolabeled products and reliable PET diagnosis, and ensure stable production and supply of radiopharmaceuticals.